Remote blood collection in reindeer (Rangifer tarandus tarandus L): a preliminary study - Wiklund, E.; Goddard, P.J.; Rehbinder, C. (Rangifer, 1994)
Automatic blood sampling equipment (ABSE) was used successfully to collect blood samples from two reindeer. During blood sampling, two methods of restraint were applied which caused no short term changes in plasma concentrations of urea, aspartate aminotransferase, alanine aminotransferase or total protein. Plasma Cortisol concentrations were significantly elevated by the two restraint techniques. The value of ABSE in studies of stress in reindeer is discussed.